1997
DOI: 10.1161/01.hyp.30.3.664
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effect of PGE 2 and PGI 2 on Renal Function

Abstract: Rapid degradation of prostacyclin (PGI2) inherent to its molecular structure has long been a major limitation in assessing the natriuretic effect of this prostaglandin. The recent availability of the stable PGI2 analogue iloprost now allows for a comparative study with prostaglandin E2 (PGE2). In the present study conducted in six anesthetized dogs, the intrarenal effects of two consecutive doses (1 and 4 ng x kg(-1) x min(-1)) of PGE2 on renal blood flow, glomerular filtration rate, and urinary sodium excreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 6 publications
3
12
0
Order By: Relevance
“…The finding does, however, support the hypothesis that iloprost has a natriuretic effect, thus explaining the increase in urinary output reported by other authors [20]. Moreover, we found in our experimental model that iloprost increased the urinary flow rate, as also observed by Ylitalo et al [21], and this increase should be considered secondary to the direct action of iloprost.…”
Section: Discussionsupporting
confidence: 87%
“…The finding does, however, support the hypothesis that iloprost has a natriuretic effect, thus explaining the increase in urinary output reported by other authors [20]. Moreover, we found in our experimental model that iloprost increased the urinary flow rate, as also observed by Ylitalo et al [21], and this increase should be considered secondary to the direct action of iloprost.…”
Section: Discussionsupporting
confidence: 87%
“…Here, we found that CTGF is mediated by PGE 2 . Our data is consistent with previous reports that PGE 2 influences renal vascular resistance, causing an increase in renal vascular cAMP levels and inducing relaxation of preglomerular vessels 24,25 , while PGI 2 was a less likely candidate to mediate CTGF because it is less potent as a renal vasodilator 13,26 . Furthermore, our finding that CTGF prostanoids are derived from the CNT rather than the Af-Art endothelium (see below), supports the hypothesis that PGE 2 is the mediator of CTGF, since PCR studies have shown that connecting tubules express mPGES, the enzyme that synthesizes PGE 2 , while PGI 2 synthase is not expressed in the nephron 27 .…”
Section: Discussionsupporting
confidence: 93%
“…This would result in enhanced NO concentrations, which in turn would increase diffusion, thus enhancing the effects of NO in vascular smooth muscle cells. Third, other modulators of vascular tone, such as prostaglandins (5,11,21,63), carbon monoxide (CO) (8,29,67,68), cytochrome P-450 epoxygenase products (15,27,66), and endothelium-dependent hyperpolarizing factor (48,64), could be upregulated in the knockouts, mitigating the reduced vasodilator effect of NO in the vasculature. Finally, other aquaporins may compensate for the lack of AQP-1 within the vasculature.…”
Section: Discussionmentioning
confidence: 99%